Information Literacy Instructions, Digital Resource Integration, and Students’ Academic Success - Canaria, Mary Joy C (2024)
In the contemporary higher education landscape, the fusion of information literacy education and seamless integration of digital resources is imperative for fostering students' academic success amidst a surge in information flow and technological progression. Educational institutions, including the San Pedro College of Business Administration (SPCBA) in the Philippines, strive to synchronize with the evolving demands of the 21st century by prioritizing the roles of information literacy instruction and digital resource integration in shaping students' academic trajectories. This study aimed to elucidate the intricate relationship between information literacy instruction, digital resource integration, and academic success at SPCBA. Data collected from 180 college students through survey questionnaires revealed a high level effectiveness of information literacy, robust digital resource integration, and significant academic success. Correlation analyses uncovered moderate associations between information literacy instruction and digital resource integration, as well as between information literacy instruction and academic success. Additionally, digital resource integration exhibited a significant correlation with academic success. Regression analysis further highlighted that information literacy instruction significantly predicts academic success, especially when combined with digital resource integration. In light of these findings, recommendations were proposed to enhance information literacy programs, integrate digital resources into curricula, foster collaboration between faculty and librarians, and conduct regular assessments for improvement. This study contributes to the literature on information literacy, digital resource integration, and academic success, providing insights for optimizing student learning outcomes in the digital age. Further research is encouraged to explore the nuanced dynamics of this relationship and develop targeted interventions for educational enhancement.